Public Interest Litigation in India : Overreaching or Underachieving? - Gauri, Varun (2012)
Public interest litigation has historically been an innovative judicial procedure for enhancing the social and economic rights of disadvantaged and marginalized groups in India. In recent years, however, a number of criticisms of public interest litigation have emerged, including concerns related to separation of powers, judicial capacity, and inequality. These criticisms have tended to abstraction, and the sheer number of cases has complicated empirical assessments. This paper finds that public interest litigation cases constitute less than 1 percent of the overall case load. The paper argues that complaints related to concerns having to do with separation of powers are better understood as criticisms of the impact of judicial interventions on sector governance. On the issue of inequality, the analysis finds that win rates for fundamental rights claims are significantly higher when the claimant is from an advantaged social group than when he or she is from a marginalized group, which constitutes a social reversal, both from the original objective of public interest litigation and from the relative win rates in the 1980s.